A molecular phylogeny for the Pacific monitor lizards (Varanus subgenus Euprepiosaurus) reveals a recent and rapid radiation with high levels of cryptic diversity. Issue 4 (14th March 2019) - Weijola, Valter; Vahtera, Varpu; Lindqvist, Christer; Kraus, Fred
Abstract: We provide a geographically well-sampled, time-calibrated molecular phylogeny for the Pacific monitor lizards ( Varanus : subgenus Euprepiosaurus ) based on ND4 and 16S rRNA mitochondrial DNA sequences. Three well-supported clades, or species groups, are retrieved: the Varanus doreanus Group, the V. jobiensis Group and the V. indicus Group. The subgenus is estimated to have originated in the Mid-Miocene, but extant lineage diversification dates from the Late Miocene and Pliocene. A rapid and widespread radiation of the V. indicus Group into the South-West Pacific islands has occurred in the Pleistocene, but colonization onto these islands did not occur in a linear, stepping-stone fashion. Genetically distinct populations – by tradition classified as V. indicus, but seemingly representing distinct species – occur scattered on Tanimbar, several of the Solomon Islands, the Admiralty Islands, the Louisiade Archipelago, Palau and Guam. Our analyses indicate that Varanus jobiensis is a species complex with several divergent lineages that started to separate in the Pliocene and continued in the Pleistocene, the former coinciding with the uplift of the Central Dividing Range on New Guinea. We find that sympatry among species of Euprepiosaurus has not occurred until divergence times of 4.7–5.8 Myr have accrued.